Utility of renal replacement therapy in poisoning and drug overdosage - Rohit Bhowmick; Sasidaran Kandasamy (Journal of Pediatric Critical Care)
Toxic and prescribed drug ingestions are a significant cause of pediatric morbidity and mortality. Management of the poisoned patient begins with a thorough evaluation, identification of the agent(s) involved, and assessment of severity and symptoms. Therapy consists of the provision of supportive care, prevention of poison absorption, use of antidotes, and, when appropriate, the use of renal replacement therapy (RRT) to enhance the elimination of the poison. Among several elimination techniques, extracorporeal treatment such as RRT can be lifesaving as it rapidly removes the toxin independent of the patient’s indigenous clearance. Hemodialysis remains the most commonly used RRT for toxin removal, and the role of continuous RRT and therapeutic plasma exchange is emerging. To properly utilize the RRT, the clinician should understand the chemical properties of the toxins and the underlying mechanism of clearance by the concerned RRT technique. Although pediatric literature is mainly limited to case reports, timely initiation of RRT helps manage children with poisoning and drug overdose.